Prayer Leads to Advocacy: The Theological Logic in a Bishop's Statement on Comprehensive Immigration Reform - Vining, James W. (Frontiers in Communication, 2022)
This paper contributes to the scholarly discussions about the role of religion in social action rhetoric by revealing the complexities and abundance of rhetorical resources found in the logic of theology. To this end, I explored rhetorical functions of theology within Bishop Michael Burbidge's 2013 Statement on Comprehensive Immigration Reform. Close textual analysis of the text allows for the identification of what I call the “textual theology” - a mediating level of theology between theological traditions and the rhetoric in a text. Analysis of the textual theology in the Bishop’s statement provides insights as to how the more abstract levels of theology animate texts in the real world in ways that have implications that reach beyond the particular text.